Learning local anesthetic techniques in dental college of Purvanchal Region, India: A cross-sectional questionnaire study - Keshav Kumar; P G Naveen Kumar (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dentistry deals with teeth and related oral structures. Most of the procedure require anesthesia to make it painless. Objective: The objective of this study was (1) Recording the most frequently used local anesthetic techniques in our dental colleges and (2) satisfaction rate of dental students toward their curriculum of learning local anesthesia. Finally, we also wanted to formulate a research hypothesis, i.e., will artificial models be able to restitute conventional ways of learning local anesthesia in dental colleges. Materials and Methods: Prevalidated questions from published articles were picked and using Google Forms, an online survey platform was prepared, students who were the part of the study were asked to mark their response. Out of 90 students, 74 replied to the questionnaire. Response rate was 82.22%. This study was conducted between April and June 2019. Results: The survey results show that inferior alveolar nerve block and greater palatine were used very frequently (75.7% and 58.1%), respectively. Whereas, papillary (interdental) injection (PI) rarely (43.2%) or never (24.3%) and mental/incisive nerve block rarely (31.1%) or never (10.8%). Fifty-eight percent reported to learn local anesthesia on patient. Two-third (67.6%) of students was satisfied with their routine way of learning local anesthesia. Conclusion: Our study infers that, inferior alveolar nerve block is very frequently used nerve block. PI is rarely or never used block. Maxillary infiltration is marked as easy technique and can be performed without getting additional training. Two-third of students are satisfied with the present dental curriculum while one third wants a change.